Fostering Sustainability @UniTs - Paolo Bevilacqua; Barbara Campisi; Patrizia De Luca; Gianluigi Gallenti; Ilaria Garofolo (Universitas Diponegoro, 2021)
Promoting sustainability through innovative culture and models is nowadays a top task for universities. Their commitment oriented by the 17 United Nations’ Sustainable Development Goals (UN SDGs) conveys the message that sustainability is not a